A Literature Review of Work From Home Phenomenon During COVID-19 Toward Employees’ Performance and Quality of Life in Malaysia and Indonesia - Abiddin, Norhasni Zainal; Ibrahim, Irmohizam; Abdul Aziz, Shahrul Azuwar (Frontiers in Psychology, 2022)
The purpose of this paper is to determine the performance of employees employed at home during the COVID-19 pandemic in Malaysia and Indonesia, also to examine the employee’s quality of life affected by COVID-19. The current study is aimed to critically determine the performance of employees employed at home during the COVID-19 pandemic. The author has analyzed and reviewed various sources of articles, reports, and documents from previous research and literature. The findings explain that working from home has provided advantages and disadvantages for both the employees and the organization and is responsible for the decrease in employee productivity. In addition, the findings conclude that the fact that working from home is generally not feasible because many areas of work cannot be done from home, although for many employees, working from home has provided a work-life balance.